2020
DOI: 10.1159/000505667
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Moderate Weight Loss on a Non-Invasive Biomarker of Liver Fibrosis: A Randomised Controlled Trial

Abstract: Background: Referral to weight loss programmes is the only effective treatment for nonalcoholic fatty liver disease (NAFLD). Clinicians should advise weight loss and screen for liver fibrosis using the Enhanced Liver Fibrosis (ELF) score. Aim: To examine if the ELF score changes with weight loss. Design and Setting: Randomised controlled trial (ISRCTN85485463) in UK primary care during 2007-2008. Method: Adults with a BMI of 27-35 kg/m 2 and ≥1 risk factor for obesity-related disease were randomised to attend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…10 Weight change was also positively associated with changes in FIB-4, a noninvasive fibrosis marker. Previous research found no evidence of changes in another noninvasive fibrosis marker, the Enhanced Liver Fibrosis score, following weight loss in an unselected population with overweight and possible moderate fibrosis, 26 but reductions in magnetic resonance measured liver stiffness with weight loss in NAFLD. 27 Identifying noninvasive biomarkers of NASH and fibrosis that are responsive to change is crucial for routine monitoring.…”
Section: Discussionmentioning
confidence: 89%
“…10 Weight change was also positively associated with changes in FIB-4, a noninvasive fibrosis marker. Previous research found no evidence of changes in another noninvasive fibrosis marker, the Enhanced Liver Fibrosis score, following weight loss in an unselected population with overweight and possible moderate fibrosis, 26 but reductions in magnetic resonance measured liver stiffness with weight loss in NAFLD. 27 Identifying noninvasive biomarkers of NASH and fibrosis that are responsive to change is crucial for routine monitoring.…”
Section: Discussionmentioning
confidence: 89%
“…Also, as opposed to one of the shortcomings reported for NFS testing, the results of ELF testing do not appear to fluctuate based on obesity. One randomized study has demonstrated that moderate weight loss did not affect the ELF score significantly [ 27 ].…”
Section: Noninvasive Serum Biomarkers Targeting Collagen Turnover and Extracellular Matrix Remodelingmentioning
confidence: 99%